Eutrophication effects on fatty acid profiles of seston and omnivorous fish in tropical reservoirs - Dal'Olio Gomes, Aline; Gomes, Fernando Ribeiro; Gücker, Björn; Tolussi, Carlos Eduardo; Figueredo, Cleber Cunha; Boëchat, Iola Gonçalves; Maruyama, Lídia Sumile; Oliveira, Lucas Chagas; Muñoz-Peñuela, Marcela; Pompêo, Marcelo Luiz Martins; de Lima Cardoso, Rayssa [UNESP]; Marques, Victor Hugo; et al. (Elsevier, 2021)
It has been postulated that eutrophication causes replacement of n3 highly unsaturated fatty acids (n3 HUFA) rich taxa, such as Bacillariophyta, Cryptophyta and Dinophyta, with taxa poor in these fatty acids (FA), such as Chlorophyta and Cyanobacteria. Such a change in community composition at the basis of the food web may alter the FA composition of consumer tissues. Here, we investigated the effects of eutrophication on phytoplankton composition and FA profiles of seston and muscle of two omnivorous fish species (Astyanax fasciatus and Astyanax altiparanae) from reservoirs of different trophic status in Southeast Brazil. The phytoplankton composition and seston FA profiles reflected the degree of eutrophication at most of the studied sites. Three of the five most eutrophic sites were dominated by cyanobacteria and had the highest saturated fatty acid (SFA) and lowest polyunsaturated fatty acid (PUFA) relative contents among all sites. In contrast, the remaining two sites presented a higher phytoplankton diversity and higher relative contribution of sestonic PUFAs with 18 carbons (C18) and HUFAs than less eutrophic systems. However, there were no clear effects of sestonic FA profiles on the FA profiles of muscle of both fish species. A higher percentage of n3 HUFAs was found in the fish samples from a hypereutrophic and cyanobacteria dominated reservoir than in those from sites with a more diverse phytoplankton community in which fish mainly showed higher percentages of C18 PUFA. These results suggest a lack of a direct relationship between the degree of eutrophication and the percentage of n3 HUFAs in both fish species, which can be caused by specific characteristics of the reservoirs that may modulate eutrophication effects. Therefore, consumer FA biochemistry seemed to be dictated by their ability to select, accumulate, and modify dietary FAs, rather than by the eutrophication degree of the studied tropical reservoirs.
Keywords: Astyanax; Phytoplankton; Polyunsaturated fatty acids; Trophic transfer; Water pollution